STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN PARTISIPASI SISWA KELAS V SDN LEBAK KEPUH 1 - Khairunnisa Khairunnisa; Vira Yuniar; Desty Endrawati Subroto (CV. Denasya Smart Publisher, 2025)
This research was conducted in the fifth-grade class of SDN Lebak Kepuh 1 to examine active learning in the classroom that focuses on a student-based learning approach. This approach is important in encouraging students' critical thinking skills. The teacher is the main factor that influences students' motivation to actively participate in class discussions. The study aims to evaluate the role of the teacher as well as strategies that can be implemented to increase student activeness. The purpose of this study is to find out active learning strategies to increase the participation of fifth grade students at Lebak Kepuh 1 State Elementary School in the 2024/2025 school year. The study also highlights the teacher's contribution in motivating students and effective solutions to overcome learning obstacles. The method used is a literature study, with the results showing three main roles of the teacher as a facilitator, classroom time manager, and constructive feedback giver.